1999
DOI: 10.1046/j.1525-1438.1999.99055.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of cervical cancer and feasibility of screening in rural China: a pilot study for the Shanxi Province Cervical Cancer Screening Study

Abstract: For cervical cancer screening to be feasible in developing countries, it must be accurate, inexpensive, and easy to administer. We conducted a pilot study in rural Shanxi Province, People's Republic of China, to determine disease prevalence and study feasibility in preparation for a large-scale comparative trial of 6 screening tests. One-hundred and thirty-six nonpregnant women with no history of hysterectomy, pelvic radiation, or Papanicolaou tests were screened in a rural clinic. Ten percent of the women enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 19 publications
4
24
0
Order By: Relevance
“…No HSIL was found in 502 biopsies from the HPVÀ/CYTOÀ subset. This is concordant with the Guanacaste study (Bratti et al, 2004: 0 HSIL out of 150) and the Shanxi study (Belinson et al, 1999(Dr R Gerald Pretorius, personal communication, January 2005: 0 HSIL out of 1274). In total, no HSIL was found in 1926 biopsies from HPVÀ/CYTOÀ subset.…”
Section: Hpv/cyto Subsetssupporting
confidence: 84%
See 2 more Smart Citations
“…No HSIL was found in 502 biopsies from the HPVÀ/CYTOÀ subset. This is concordant with the Guanacaste study (Bratti et al, 2004: 0 HSIL out of 150) and the Shanxi study (Belinson et al, 1999(Dr R Gerald Pretorius, personal communication, January 2005: 0 HSIL out of 1274). In total, no HSIL was found in 1926 biopsies from HPVÀ/CYTOÀ subset.…”
Section: Hpv/cyto Subsetssupporting
confidence: 84%
“…Then, the number of abnormal cells per sample would be much more important and, consequently, the sensitivity gap between HPV and cytology for detection of HSIL would be much smaller. This idea is supported in the literature, as studies performed in a high-risk population demonstrated relatively small gaps (4, 10, 10 and 15%) (Belinson et al, 1999;Kuhn et al, 2000;Schiffman et al, 2000;Wright et al, 2000) compared with studies performed in a low-risk population with higher gaps (30, 38, 54 and 55%) (Ratnam et al, 2000;Clavel et al, 2001;Kulasingam et al, 2002;Petry et al, 2003).…”
Section: Contribution Of Hpv Viral Load Studymentioning
confidence: 83%
See 1 more Smart Citation
“…However, the TCT is costly as compared to the Pap test and requires specialized equipment and skilled personal, thus is application in clinical practice has been slow. Screening a large, rural population must take into consideration the sensitivity and specificity of the testing, ease of administration, and costs involved (Belinson et al, 1999). Although there have been a number of studies evaluating different methods and screening programs for cervical cancer in China, no ideal one has been identified (Belinson et al, 1999;Belinson et al, 2001;Belinson, 2002;Pan et al, 2003;Li et l., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The ThinPrep cytological test (TCT), a liquid-based method has been shown to have an increased sensitivity over that of the Pap test in screening for cervical cancer; however, it is more costly and requires specific equipment and specially trained personnel (Abulafa et al, Carns ey al., 2008). However, screening of very large numbers of individuals in a largely rural setting is associated with significant costs and logistical difficulties (Belinson et al, 1999;Belinson et al, 2001;Belinson, 2002;Pan et al, 2003;Li et al, 2009). Currently, the TCT has not been widely applied in China.…”
Section: Introductionmentioning
confidence: 99%